Effect of prenatal and postnatal malnutrition on intellectual functioning in early school-aged children in rural western China. Issue 31 (August 2016) - Li, Chao; Zhu, Ni; Zeng, Lingxia; Dang, Shaonong; Zhou, Jing; Yan, Hong
Abstract : Abstract: The aim of this study was to evaluate the effect of prenatal and postnatal malnutrition on the intellectual functioning of early school-aged children. We followed the offspring of women who had participated in a trial of prenatal supplementation with different combinations of micronutrients and who remained resident in the study field. We measured their intellectual functioning using the Wechsler intelligence scale for children (WISC-IV). Height-for-age, weight-for-age, and body mass index (BMI)-for-age were used as anthropometric nutritional status indices. Four of the 5 composite scores derived from the WISC-IV, except for working memory index (WMI), were significantly lower in low birth weight children after adjusting for confounds. All 5 composite scores, including full-scale intelligence quotient (FSIQ), verbal comprehension index (VCI), WMI, perceptual reasoning index (PRI), and processing speed index (PSI) were significant lower in stunted and underweight children. The differences in the means of WISC-IV test scores were greatest between stunted and nonstunted children. The means for FSIQ, VCI, WMI, PRI, and PSI were as follows: 5.88 (95% confidence interval [CI]: 2.84–8.92), 5.08 (95% CI: 1.12–8.41), 4.71 (95% CI: 1.78–7.66), 6.13 (95% CI: 2.83–9.44), and 5.81 (95% CI: 2.61–9.00). These means were lower in stunted children after adjusting for confounds. Our results suggest the important influences of low birth weight and postnatal malnutrition (stunting, low body weight) on intellectual functioning in early school-aged children.